Determining the water needs of dairy cattle - Potts, Justin C. (Kansas State University, 2012)
Data obtained from 50 individual published studies recording water intake by dairy cattle were utilized in a meta-analysis to develop a prediction equation for free water intake (FWI). Studies were selected based on quantitative measurements of DMI, diet DM%, water intake (WI), and milk yield. Many of the studies determined FWI on multiple treatments resulting in 116 mean data points from the 50 studies. With the addition of Na in the meta-analysis, 40 data points were available from the studies to examine the effects of Na on FWI. The effects of DMI, ration water intake (RWI), and milk yield (MY) were used to develop a FWI prediction equation from the 116 data points. The effects of DMI, RWI, MY, and sodium intake were used to develop a second prediction equation from the 40 data points. These equations were then compared with five published FWI prediction equations from Castle and Thomas (1975), Dahlborn et al. (1998), Little and Shaw (1978), Murphy et al. (1983) and Stockdale and King (1983). This data set showed that the five published equations either over or under predicted (P < 0.05) FWI when compared the actual FWI calculated from the meta-analysis data points. It also showed that the equation developed from the meta-analysis data points is the more accurate in determining FWI from the data points selected from the studies. A second project was conducted with the fresh water data collected from 13 freestall (FS) and 11 dry lot (DL) Kansas dairies over a 10-year period (2000-2009). Fresh water was recorded from water pumping records. Data were first summarized annually by operation and then converted to a per cow per day basis prior to analysis. Data were then analyzed by using the mixed procedures of SAS. Fixed effects included in the model were dairy type (FS or DL) and year was considered a random effect. The DL dairies averaged 186 L/cow per day and were lower than the FS dairies which averaged 237 L/cow per day. Differences between DL and FS style dairies may have been due to differences in parlor fresh water usage or cow cooling systems.
Keywords: Water intake; Dairy water; Animal Sciences (0475)